1)3х^2-28х+9=0
D = b^2 - 4 * a * c = (-28)^2 - 4 * (3) * (9) = 676
x1 = (-b + sqrt(D)) / (2*a)
x2 = (-b - sqrt(D)) / (2*a)
x1 = 9
x2 = 1/3
2)2х^2-8х+11=0
D = b^2 - 4 * a * c = (-8)^2 - 4 * (2) * (11) = -24
___
I*\/ 6
x1 = 2 +
2
___
I*\/ 6
x2 = 2 -
2
3)16х^2-8х+1=0
D = 0, то корень всего один.
x = -b/2a = --8/2/(16)
x = 1/4
4)7х^2-21=0
D = b^2 - 4 * a * c =
(0)^2 - 4 * (7) * (-21) = 588
___
x1 = \/ 3
___
x2 = -\/ 3
б)(2х-b)²=4x²-4xb+b²
в)(b+3)(b-3)=b²-9
г)(5у-2х)(5у+2х)=25y²-4x²
2Упростите выражение:
(с+b)(с-b)-(5c²-b²)=c²- b² - 5c²+b²=-4c²
3Разложите на множители
а)25у²-а²=(5y-a)(5y+a)
б)с²+4bc+4b²=(c+2b)²
4Решите уравнение
12-(4-Х)²=х(3-х)
12-16+8x-x²=3x-x²
8x-x²-3x+x²=16-12
5x=4
x=0,8
5 Выполните действия
а)(3х+у²)(3х-у²)=9x²-y^4
б)(а³-6а)²=a^6-12a^4+36a²
в)(а-х)²(х+а)=(a²-2ax+x²)(x+a)=a²x+a³-2ax²-2a²x+x³+ax²=-a²x+a³-ax²+x³
6Решите уравнение
а)(4х-3)(4х+3)-(4х-1)²=3х
16x²-9-16x²+8x-1-3x=0
5x-10=0
5x=10
x=2
б)16с²-49=0
c²=49/16
c1=7/4=1,75 c2=-7/4=-1,75
7Разложите на множители
а)100а4 - 1/9b² =(10a²-1/3b)(10a²+1/3b)
б)9х²-(х-1)²=(3x+x-1)(3x-x+1)=(4x-1)(2x+1)